Thermoregulatory ability and mechanism do not differ consistently between neotropical and temperate butterflies - Laird-Hopkins, Benita C; Ashe-Jepson, Esme; Basset, Yves; Arizala Cobo, Stephany; Eberhardt, Lucy; Freiberga, Inga; Hellon, Josh; Hitchcock, Gwen E; Kleckova, Irena; Linke, Daniel; Lamarre, Greg P A; McFarlane, Alex; et al. (Global change biology, 2023)
Climate change is a major threat to species worldwide, yet it remains uncertain whether tropical or temperate species are more vulnerable to changing temperatures. To further our understanding of this, we used a standardised field protocol to (1) study the buffering ability (ability to regulate body temperature relative to surrounding air temperature) of neotropical (Panama) and temperate (the United Kingdom, Czech Republic and Austria) butterflies at the assemblage and family level, (2) determine if any differences in buffering ability were driven by morphological characteristics and (3) used ecologically relevant temperature measurements to investigate how butterflies use microclimates and behaviour to thermoregulate. We hypothesised that temperate butterflies would be better at buffering than neotropical butterflies as temperate species naturally experience a wider range of temperatures than their tropical counterparts. Contrary to our hypothesis, at the assemblage level, neotropical species (especially Nymphalidae) were better at buffering than temperate species, driven primarily by neotropical individuals cooling themselves more at higher air temperatures. Morphology was the main driver of differences in buffering ability between neotropical and temperate species as opposed to the thermal environment butterflies experienced. Temperate butterflies used postural thermoregulation to raise their body temperature more than neotropical butterflies, probably as an adaptation to temperate climates, but the selection of microclimates did not differ between regions. Our findings demonstrate that butterfly species have unique thermoregulatory strategies driven by behaviour and morphology, and that neotropical species are not likely to be more inherently vulnerable to warming than temperate species.
Keywords: Humans; Temperature; vysoká teplota; Hot Temperature; teplota; tropics; nízká teplota; Butterflies; ecophysiology; lidé; microclimate; zvířata; ectotherms; Cold Temperature; insects; climate change; behaviour; Body Temperature Regulation; Lepidoptera; Animals; motýli; termoregulace